A novel summer - Brenner, Jamie, 1971- (Park Row Books, 2024)
In her return to Provincetown after a best-selling novel exposes local secrets, an author returns to her idyllic Cape Cod hometown to face her betrayal but rediscovers her passion and community through a summer managing a friend's bookstore.